2015
DOI: 10.5812/aapm.23565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Midazolam and Sufentanil to Intrathecal Bupivacaine on Analgesia Quality and Postoperative Complications in Elective Cesarean Section

Abstract: Background:Intrathecal adjutants can be used for regional anesthesia (RA) in cesarean section to improve its quality in terms of time and complications. Some previous studies focused on the effects of adding sufentanil and/or midazolam to bupivacaine and compared each with using bupivacaine alone. However, there has been no study to assess the effects of using sufentanil and midazolam in combination with bupivacaine.Objectives:The aim of this study was to evaluate and compare properties (time of achievement/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
0
28
0
5
Order By: Relevance
“…Sufentanil: Data on the incidence of shivering with IT sufentanil (5 RCTs, n=156 patients) were available in all the studies. [18][19][20][21][22] The mixed evidence from the network meta-analysis showed that the incidence of the shivering was not signi cantly lower with IT sufentanil when compared to the control group. (IT Sufentanil vs. Control: 23.71% vs. 45.28%; OR: 0.37; 95% CrI: 0.11 to 1.22; P = 0.23).…”
Section: Resultsmentioning
confidence: 99%
“…Sufentanil: Data on the incidence of shivering with IT sufentanil (5 RCTs, n=156 patients) were available in all the studies. [18][19][20][21][22] The mixed evidence from the network meta-analysis showed that the incidence of the shivering was not signi cantly lower with IT sufentanil when compared to the control group. (IT Sufentanil vs. Control: 23.71% vs. 45.28%; OR: 0.37; 95% CrI: 0.11 to 1.22; P = 0.23).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one potentially relevant articles were identified from 115 citations. Twenty-one studies consisting of 1433 patients (Control group: 590 patients in twenty-one studies; Fentanyl group:199 patients in seven studies [11][12][13][14][15][16][17] ; Sufentanil group: 156 patients in five studies [18][19][20][21][22] ; Meperidine group: 488 patients in ten studies 15,[23][24][25][26][27][28][29][30][31] ) contained data regarding the effect of IT opioids on shivering (Flow chart: Figure 1). Table 1a and 1b summarises the systematic review of the effects of IT fentanyl, sufentanil and meperidine on shivering in women undergoing cesarean delivery.…”
Section: Resultsmentioning
confidence: 99%
“…An additional 16 papers were excluded on more detailed review for the following reasons: no shivering recorded (n=5), no placebo group (n=10), and added other anti-shivering drugs (n=1). The remaining 8 studies met our selection criteria and were included in the meta-analysis [ 16 – 18 , 24 – 28 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intrathecal sufentanil added to bupivacaine, as compared with fentanyl, may prolong duration of analgesia, facilitate the spread of the sensory block, increase mean pulse oximetry levels, and reduce overall adverse effects. De Figueiredo [ 15 ] reported that the addition of sufentanil to hyperbaric bupivacaine and morphine during spinal anesthesia for cesarean section decreased the incidence of shivering during the immediate postoperative period; however, some other studies found that intrathecal sufentanil did not reduce shivering [ 16 – 18 ]. Hoshijima et al [ 19 ] found that remifentanil was associated with an increased incidence of postoperative shivering compared with alfentanil or fentanyl, but no significant difference was seen when compared with sufentanil.…”
Section: Introductionmentioning
confidence: 99%